1986
DOI: 10.1080/00288233.1986.10430466
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of pesticides toAllobophora caliginosa(Oligochaeta : Lumbricidae)

Abstract: Juvenile (4-week-old) earthworms reared in a laboratory were kept individually for 7 days in soil treated with several concentrations of various pesticides. Mortality and weight change were recorded. The relative toxicity of each pesticide-i.e., the cOlicentration (mg/kg of dry soil) of pesticide causing zero growth-compared with the standard, carbofuran (0.10), was aldicarb (0.09), phorate (0.30), aldoxycarb (0.40), methomyl (0.54), ox amyl (0.59), isazophos (0.93), fenamifos (5.72), fensulfothion (7.35), dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 30 publications
0
17
2
1
Order By: Relevance
“…Although Martin (1986) suggested that juveniles might be more sensitive to pesticides than adults, the mean number and biomass of hatchlings produced per cocoon in both the treatments were not signi"cantly di!erent from that of controls. Mancozeb, therefore, had no e!ect on the number and/or biomass of the hatchlings produced.…”
Section: Discussioncontrasting
confidence: 57%
“…Although Martin (1986) suggested that juveniles might be more sensitive to pesticides than adults, the mean number and biomass of hatchlings produced per cocoon in both the treatments were not signi"cantly di!erent from that of controls. Mancozeb, therefore, had no e!ect on the number and/or biomass of the hatchlings produced.…”
Section: Discussioncontrasting
confidence: 57%
“…Carbendazim and carbofuran have well known toxicity to native and exotic species of several earthworm families (Haque and Ebing, 1983;Gough, 1986;Martin, 1986;Panda and Sahu, 2004;Ellis et al, 2010;Tripathi et al, 2010;De Silva et al, 2010), while glyphosate generally has non-toxic or less-toxic effects (Dalby et al, 1995;Yasmin and D'Souza, 2007). Most herbicides are less toxic to earthworms than insecticides and fungicides, although some can be lethal, depending on the active ingredient (Edwards and Bohlen, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Studies found in the literature on the effect of pesticides on earthworms were conducted either under laboratory conditions (Bauer and Römbke 1997;Cathey 1982;RodriguezCastellanos and Sanchez-Hernandez 2007;Brulle et al 2010;Muthukaruppan and Paramasamy 2010) or in the field (Martin 1986;Reddy and Reddy 1992). Evaluation was achieved using different indicators that were investigated at various organisation levels.…”
Section: Had Greatermentioning
confidence: 99%